Strengthening rural youth participation in Family Farmer organizations in MERCOSUR. The case of REAF (Specialized Meeting on Family Farming) - González, Leticia (Facultad de Ciencias Políticas y Sociales, 2020)
This article analyzes the experience of Rural Youth working group of the Family Farming Specialized Meeting of MERCOSUR between 2007 and 2018 in order to recognize the actions developed to strengthen the leadership of rural youth into Family Farming Organizations and to discourage migration. Taking into account that rural youth do not use to lead these organizations in our region, we aim to think about youth possibilities and limitation to play these roles and strategies developed to promote rootedness.